High anesthetic (isoflurane) indoor pollution is associated with genetic instability, cytotoxicity, and proliferative alterations in professionals working in a veterinary hospital - Figueiredo, Drielle B. S. [UNESP]; Aun, Aline G. [UNESP]; Souza, Kátina M. [UNESP]; Nishimoto, Igor H. [UNESP]; Silva, Mariane A. P. [UNESP]; Carvalho, Lídia R. de [UNESP]; Braz, Leandro Gobbo [UNESP]; Braz, Mariana Gobbo [UNESP] (Springer Nature, 2022)
This is the first study to monitor anesthetic pollution in veterinary operating rooms (VOR) and assess the toxicological impact of the inhalational anesthetic isoflurane (exposed group) compared to matched volunteers (control group). DNA damage was evaluated in mononuclear cells by the comet assay while genetic instability (including micronucleus-MN), cell proliferation, and cell death markers were assessed by the buccal MN cytome assay. Residual isoflurane concentrations in VOR (air monitoring) lacking the scavenging system were assessed by infrared spectrophotometry; the mean concentration was 11 ppm (≥ 5 times above the international recommended threshold). Comet assay results did not differ between groups; however, both younger exposed professionals (with higher week workload) compared to older individuals exposed for the same period and older professionals with greater time of exposure (years) compared to those in the same age group with fewer years of exposure presented higher DNA damage. The exposed group had a higher frequency of MN, nuclear buds, binucleated cells, karyorrhexis, and karyolysis and a lower frequency of basal cells than the control group. Exposed women were more vulnerable to genetic instability and proliferative index; exposed men presented more cytotoxicity. High WAG exposure has deleterious effects on exposed professionals.
Keywords: Biomonitoring; DNA damage; Genetic instability; Indoor air pollution; Inhalation anesthetic; Oral cavity